Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Produktivitas Kerja Pada Karyawan Resto Omah Kalang - Fahmi Suweleh; Jumadi (CV. ITTC INDONESIA, 2025)
This research was conducted to determine the extent to which work discipline and compensation affect the productivity levels of Omah Kalang Restaurant employees. The research method used in this study is quantitative with a survey approach. The respondents of this study were 37 employees of Omah Kalang Restaurant, thus the sampling technique used was saturated sampling/census. Data was collected through Likert-scale questionnaires with 5 levels. The results show that work discipline has a positive influence with a significance value of 0.000 < 0.05, while compensation shows no influence with a significance value of 0.240 > 0.05. Simultaneously, both variables have a significant influence with an F-value of 33.071 and a coefficient of determination (Adjusted R2) of 0.641, meaning that 64.1% of work productivity is influenced by work discipline and compensation. In conclusion, good work discipline and appropriate compensation together are able to increase employee work productivity